1982
DOI: 10.1029/ja087ia12p10536
|View full text |Cite
|
Sign up to set email alerts
|

Observations of parallel ion energization in the equatorial region

Abstract: In this paper we examined in detail an example of bounce‐phase‐clustered ions such as earlier reported by McIlwain (1976), Quinn (1978) and Quinn and McIlwain (1979). The cluster has small pitch angle, but investigation of the energy time dispersion properties of the cluster reveals that it was formed at the equator. The acceleration region extended over about 2.4 RE along the field direction. We suggest that the ion cluster is set up by acceleration during a transient convection surge, and we discuss the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 8 publications
3
63
0
Order By: Relevance
“…They have also been observed at geosynchronous altitude by ATS-5 and ATS-6 [Quinn and Mcllwain, 1979;Quinn and Southwood, 1982]. In as shown in the Plate la.…”
Section: Introductionmentioning
confidence: 88%
“…They have also been observed at geosynchronous altitude by ATS-5 and ATS-6 [Quinn and Mcllwain, 1979;Quinn and Southwood, 1982]. In as shown in the Plate la.…”
Section: Introductionmentioning
confidence: 88%
“…This suggests that the mechanisms of cross-tail acceleration and field collapse or dipolarization of the inner tail ("convection surge mechanism" [Lezniak and Winckler, 1970;Quinn and Southwood, 1982;Mauk, 1986]) are the major mechanisms responsible not only for ion acceleration and injection but also for electron injections in the inner magnetotail. The test orbits show that the electric field associated with the collapse is most significant for the inner edge of the region of enhanced electron fluxes (injection boundary), as well as for the ion injection boundary [Birn et al, 1997b].…”
Section: Stunmary and Discussionmentioning
confidence: 99%
“…Early studies of the energetic electrons' pitch angle distributions during substorms included both modeling work and observational work. Modeling and observation work have shown that substorm induced electric fields accelerate electrons [Moore et al, 1981;Mauk, 1986;Aggson et al, 1983;Quinn and Southwood, 1982;Hesse, 1993, 1996;Birn et al, 1998Birn et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%